Meat Productivity, Biochemical And Amino Acid Composition Of Bull Meat With Different Genotypes (Journal of Pharmaceutical Negative Results, 2022)
Purpose of this article is based on the meat productivity index, biochemical and amino acid composition of bull meat with different genotypes in a comparative aspect. Obtained data evidence some differences in the biochemical and amino acid composition of meat in experimental animals. Thus, solids content, comprising proteins, carbohydrates, fats, minerals, hormones and vitamins were 0.5% higher in the Kyrgyz meat type and 0.5% lower in the Ala-Tau breed compared to the Kyrgyz aboriginal population, where the Aulieatin breed had the same indicators as the aboriginal one. The moisture content varies from 64.4 to 68.6%, where the largest amount of it was in the meat-mince bulls of the Aulieatin group. The amount of dry substance ranged from 31.4 to 35.6 % with a high content in individuals of the Ala-Tau breed. Researchmaterials and methods: amino acids are the most important organic compounds that make up protein molecules. The studied materials on the amino acid composition of beef is the most complete in food and biological relation. Among indispensable amino acids, there are particularly important ones that are called critical, such as lysine and others. In our studies, the lysine content was highest in the Ala-Tau breed were 3223, then in the Kyrgyz meat type were 2573, in the Aulieatin breed were 2557 and in the aboriginal cattle 2486, and the average for breeds were 2710 g/100 g of meat. The standard deviations, respectively, were: 0.416; 0.270; 0.161; 0.099 and at average 0.236 g/100 g of meat. Thus, the amount of lysine in meat of all the studied breeds of cattle was in the same content, except the Ala-Tau breed cattle. Output:based on the studied materials on meat productivity, determination of meat biochemical and amino acid composition, cattle breed standards in the market conditions of farm household in Kyrgyzstan are developed.